Quality of Service at the Religious Affairs Office, Arungkeke District, Jeneponto Regency - APRILIANA, Milda (Community Services: Sustainability Development, 2025)
Public service is an important aspect of the government system that aims to effectively, efficiently, and transparently meet the community's needs. The Office of Religious Affairs (KUA), an institution under the Ministry of Religion, is central to providing religious services, including marriage administration, religious guidance, and family consultation. This study aims to evaluate the quality of service at the KUA Arungkeke District based on the SERVQUAL theory approach, which includes five dimensions: physical evidence, reliability, Responsiveness, Assurance, and Empathy. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The study results indicate that services at the KUA Arungkeke District have generally run well, as seen by adequate facilities, employee responsiveness, and friendly and professional attitudes toward serving the community. However, several obstacles affect the quality of service, such as limited administrative equipment, delays in issuing marriage certificates due to incomplete files, and a Lack of public understanding of service procedures. However, driving factors like comfortable service spaces, reliable administrative procedures, and information transparency also increase public trust and satisfaction with the services provided. This research is expected to be used as evaluation material for the Arungkeke District KUA and provide recommendations for improving the quality of public services in the religious sector.